Tumor Endothelial Marker 8 Promotes Proliferation and Metastasis via the Wnt/β-Catenin Signaling Pathway in Lung Adenocarcinoma - Ding, Chen; Liu, Jun; Zhang, Jiali; Wan, Yang; Hu, Linhui; Charwudzi, Alice; Zhan, Heqin; Meng, Ye; Zheng, Huimin; Wang, HuiPing; Wang, Youliang; Gao, Lihua; et al. (Frontiers in Oncology, 2021)
Tumor endothelial marker 8 (TEM8), also known as ANTXR1, was highly expressed in cancers, and was identified as a biomarker for early diagnosis and prognosis in some cancers. However, the clinical role and molecular mechanisms of TEM8 in lung adenocarcinoma (LUAD) are still unclear. The present study aimed to explore its clinical value and the molecular mechanisms of TEM8 underlying the progression of LUAD. Our study found the elevation of TEM8 in LUAD cell lines and tissues. What’s more, we observed that the TEM8 expression level was associated with tumor size, primary tumor, and AJCC stage, and LUAD patients with high TEM8 expression usually have a poor prognosis. Then, we conducted a series of experiments by the strategy of loss-of-function and gain-of-function, and our results suggested that the knockdown of TEM8 suppressed proliferation, migration, and invasion and induced apoptosis in LUAD whereas overexpression of TEM8 had the opposite effect. Molecular mechanistic investigation showed that TEM8 exerted its promoting effects mainly through activating the Wnt/β-catenin signaling pathway. In short, our findings suggested that TEM8 played a crucial role in the progression of LUAD by activating the Wnt/β-catenin signaling pathway and could serve as a potential therapeutic target for LUAD.